2010 IEEE International Symposium on Industrial Electronics 2010
DOI: 10.1109/isie.2010.5637867
|View full text |Cite
|
Sign up to set email alerts
|

Application of time-series methods to disturbance estimation in predictive control problems

Abstract: Disturbance effect is a very important issue to be analyzed and considered in any control problem. Models representing the disturbance effect on the process variable are usually obtained for this purpose. These models are useful to design, for instance, classical feedforward compensators. However, when predictive control strategies are being used, no only the model capturing the disturbance effect is necessary, but that future estimations of the disturbances would be also extremely useful to get advance in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 19 publications
0
16
0
6
Order By: Relevance
“…It was shown that an improved disturbance compensator can be obtained by setting the error in the feedback structure equal to zero. This assumption can be confirmed by the GPC control law provided in Equation (8). Taking into account that the set point is set to w(j) = y(t) for j = t + d + 1, .…”
Section: Predictive Feedforward Compensatormentioning
confidence: 78%
See 3 more Smart Citations
“…It was shown that an improved disturbance compensator can be obtained by setting the error in the feedback structure equal to zero. This assumption can be confirmed by the GPC control law provided in Equation (8). Taking into account that the set point is set to w(j) = y(t) for j = t + d + 1, .…”
Section: Predictive Feedforward Compensatormentioning
confidence: 78%
“…In previous works, [8,9,24], a study of different forecasting techniques was performed in order to extend the functionality of the MPC approach. The availability of the future signal values are used to improve the prediction mechanism accuracy, which results in better performance of the MPC controller [9].…”
Section: Future Disturbance Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In industrial processes, the basic control structure consists of a feedback controller, since it is capable of providing reference tracking, while reducing the influence of plant-model mismatch and compensating for process disturbances [1,5]. It is usual that the control system only focuses on one of the listed related to the incorporation of future disturbance information [20,21]. The MPC feedback and feedforward co-design procedure results in a tradeoff, where the controller tuning procedure is carried out taking into account the most important aspects.…”
Section: Introductionmentioning
confidence: 99%